The Effect of Financial Factors on Net Income of Manufacturing Companies Listed in the JII in 2020-2024 - Pratiwi, Sefi Sindi; Faisol; Zaman, Badrus (STIE Tri Bhakti, 2025)
The background of this study is the decline in financial performance in a number of manufacturing companies incorporated in the Jakarta Islamic Index (JII), which can be seen from the fluctuation and decrease in net profit over the last three years, which is the basis for this research. Aims to explore the effect of sales, total debt, company size, inventory, and accounts receivable turnover on the net profit of manufacturing companies listed on the JII during the period 2020 to 2024. The data used in this study is secondary data taken from the company's annual financial statements. The sample consisted of 11 companies selected through purposive sampling technique. Data analysis was carried out using panel data regression with the Random Effect Model approach. The results showed that partially, sales and company size have a positive and significant effect on net profit. Conversely, total debt, inventory, and accounts receivable turnover have a significant negative effect. Simultaneously, the five independent variables are proven to have a significant influence on net income.